A Folia de Reis da família Corrêa de Goianira: uma manifestação da religiosidade popular - Silva, Maria Luiza dos Santos (2006)
SANTOS SILVA, Maria Luiza. Folia s kings of Corrêa family in Goianira: A religious grassroots manifestation. 2006. Dissertation (Master's degree) Institute Goiano of daily Pay-history and Anthropology, University Catholic of Goiás. Goiânia, 2006. In the research discoursed in this work, objective to inquire the universe where it surrounds the current events of the Folia s Kings of the Corrêa Family of the Goianira city. Initially, we approach on its concept, its geneses and consolidation in the popular Catholicism. Better to understand the historical context of begin of the Folia a Kings, we discourse on the popular Catholicism in Brazil, as well as its conflicts with the official Catholicism. We understand for official Catholicism that one seated in the ecclesiastical authority, having as center the sacramentos. Already the popular Catholicism is centered in the person of the layperson and has as religious nucleus the devotion to the saints. To analyze the Folia s Kings of the Corrêa we all made ethnography of the turn, analyzing its transformations, its relation between sacred and profane and the its system of social cohesion and solidarity. The analysis of these data comes strengthens the resistance of the popular Catholicism, today, coexisting of halfoptic form elements of the official Catholicism. For better to understand the Folia s Kings of the Corrêa de Goianira, we made a historical briefing of the origin of this city, with the arrival of the Pe. Pelágio, representing official Catholicism and, also, we rescue the origin of the family of the Corrêa, founder of the Folia s Kings in this city.